2(x+5)=3x-18

Simple and best practice solution for 2(x+5)=3x-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+5)=3x-18 equation:


Simplifying
2(x + 5) = 3x + -18

Reorder the terms:
2(5 + x) = 3x + -18
(5 * 2 + x * 2) = 3x + -18
(10 + 2x) = 3x + -18

Reorder the terms:
10 + 2x = -18 + 3x

Solving
10 + 2x = -18 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
10 + 2x + -3x = -18 + 3x + -3x

Combine like terms: 2x + -3x = -1x
10 + -1x = -18 + 3x + -3x

Combine like terms: 3x + -3x = 0
10 + -1x = -18 + 0
10 + -1x = -18

Add '-10' to each side of the equation.
10 + -10 + -1x = -18 + -10

Combine like terms: 10 + -10 = 0
0 + -1x = -18 + -10
-1x = -18 + -10

Combine like terms: -18 + -10 = -28
-1x = -28

Divide each side by '-1'.
x = 28

Simplifying
x = 28

See similar equations:

| 3cos^3(x)=3cos(x) | | x+4(3)=x+2(5) | | 6d-5-d= | | 15x+80x-10=19(5x+15) | | C/4-3=8 | | -.6t^2+4.8t=0 | | 0=4x^2+25x-21 | | 1.5-5x=11.0 | | 4y+x=-12 | | n+19=13 | | (2x^2-6x+7)-(4x^2+x-9)+(5x^2+3x-8)= | | -3(3x-6)=-9x-18 | | 0=-5T^2+37t+72 | | y=2x^2-3x+6 | | 8-8x-x^2=0 | | (2-2y+4u)(-9)= | | 0=4x^2+32x+15 | | Y-3=5-2y | | 10x+8.25=99 | | lx-3l=5x-5 | | 5x=x-14 | | 3x+y=10x-1 | | 8.25+10=99 | | W+0.04W=10.92 | | H(1)=-4.9(1)t^2+7(1)+0.6 | | (-4x+5)(-2x+7)= | | 6x+3y+8z=54 | | 12ab-4a^2(b)=0 | | -4x-6x=10-70 | | .9+m=1.1 | | 4b+2b-4=14 | | 4x^2-5x+20-(4x^2+10x)= |

Equations solver categories